P257 Sub-optimal Inhaler Technique In Patients Aged Over 75 Years. (10th November 2014) - Vandermolen, S; Berner, J; Almond, M; Huwez, F
Abstract : Introduction and objectives: NICE guidelines highlight the importance of adequate inhaler technique to ensure sufficient drug delivery in asthma and C. O. P. D. Whilst adequate inhaler technique can be a problem for patients of any age, the delivery of inhaled medication continues to be a particular problem for elderly patients. Despite the existence of pressurised metered-dose inhalers and breath-actuated inhalers, physical and cognitive impairment continues to make the use of hand-held inhalers difficult in the elderly. It is therefore likely that inhaler use in the elderly is suboptimal, regardless of device used. Methods: We assessed 50 consecutive patients aged over 75 years with C. O. P. D or asthma at our centre (mean age 78.24 ± 7.32). All had inhaler therapy prescribed prior to examination. Two observers assessed inhaler technique against guidelines adapted from the National Asthma Council of Australia 1 (see Table ). Patients used either an Evohaler (pressurised metered-dose inhaler) or Accuhaler (breath-actuated inhaler) according to their choice. Results: In the Evohaler group (25 patients), the average age was 78 (±5.5) with an average score of 6.6 (±1.81) / 10. In the Accuhaler group (25 patients), average age was 77 (±6.4) with an average score of 7.2 (±2.0) /10. 'Crucial' steps to adequate inhaler technique were also assessed. 2 The score in the Evohaler group was 4.4 (±1.2) /6, and in the Accuhaler group was 4.3 (±1.0) /6. Conclusion: This study shows that despite the availability of both Evohaler (pressurised metered-dose inhaler) and Accuhaler (breath-actuated inhaler) effective use by the elderly is still sub-optimal. The very elderly need extra support when considering and prescribing inhalers. Whilst many centres have 'good inhaler technique' as a pillar of their COPD care bundle, it may be the case that specialist services, including the use of specialist devices, directed at the elderly may help to alleviate the problems of physical and cognitive impairment when using inhalers. References: National Asthma Council Australia. Inhaler technique in adults with asthma or COPD. Melbourne: National Asthma Council Australia, 2008 Newman S. P. Inhaler treatment options in COPD. Eur Respir Rev 2005;14(96):102-108